Penerapan Algoritma Asosiasi dengan Metode Apriori Untuk Strategi Meningkatkan Hasil Penjualan Spare Part Motor - Entin Sutinah; Nani Agustina (Universitas Budi Darma, 2022)
Sales transactions in everyday life are very common, but in the sales business you must have a strategy to increase sales results optimally. This research was conducted on PD. Tri Jaya Motor, where this trading company is engaged in trading motorcycle spare parts for all types of motorcycles, both Honda, Yamaha, Kawasaki and so on. Currently PD. Tri Jaya Motor wants to make a strategy to increase sales results, but the problem is that PD. Tri Jaya Motor still doesn't get the right and effective way, one of which is in the preparation of goods that still don't have the right placement pattern, so the items that should be close together, but this stored far apart, to solve these problems a method is needed, therefore the method used in this study is the association algorithm with the a priori method to analyze motorcycle spare part sales transaction data, which in this study takes motorcycle spare part sales transaction data in one year. The purpose of this study is to find out which items are purchased by consumers simultaneously so that from this information it can be used to make sales strategies, one of which is by arranging items that are close to the items purchased by consumers simultaneously. The results of this study show that when buying a kilometer cable, 86% will buy a brake cable with a support value of 30% and 70% confidence. By knowing the products that are purchased a lot and the interrelationships between goods with one another, so the company can develop a strategy by increasing the inventory of these goods for PD. Tri Jaya Motor.